RESULTS OF RESEARCH ON SEEDS OF ECONOMIC BENTHIC SPECIES IN TIDAL REGION IN THE NORTHERN VIETNAM - Thung, Do Cong (Vietnam Journal of Marine Science and Technology, 2017)
The research results from Quang Ninh to Quang Binh have identified 14 breeding yards of mollusks and crabs along the western part of the Gulf of Tonkin, of which Quang Ninh has the largest number (4 breeding yards); Hai Phong 2 breeding yards, Thai Binh 1, Nam Dinh 2, Thanh Hoa 3 and Nghe An 2. The highest breeding density of mollusk and crab is 10 juveniles/m2 and 9 juveniles/m2 respectively. There are many indications that the breeding yards of mollusk and crab tend to decline, even by 45.9%. It is necessary to take measures to preserve the seed source by conserving mangrove forests, seagrass beds and prohibiting the forms of exploitation in the breeding season of specialty species in the tidal region.